2021
DOI: 10.1016/j.sjbs.2020.11.089
|View full text |Cite
|
Sign up to set email alerts
|

Virological surveillance, molecular phylogeny, and evolutionary dynamics of hepatitis C virus subtypes 1a and 4a isolates in patients from Saudi Arabia

Abstract: Hepatitis C virus (HCV) subtypes are pre-requisite to predict endemicity, epidemiology, clinical pathogenesis, diagnosis, and treatment of chronic hepatitis C infection. HCV genotypes 4 and 1 are the most prevalent in Saudi Arabia, however; less consensus data exist on circulating HCV subtypes in infected individuals. This study was aimed to demonstrate the virological surveillance, phylogenetic analysis, and evolutionary relationship of HCV genotypes 4 and 1 subtypes in the Saudi population with the rest of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…A recent Saudi survey conducted in Jeddah has reported that there is a lower prevalence of GT-2 (4.1%) and higher HCV genotype 4 (60.7%) [1]. Because GT4 is very common in Egypt (10%-15%) and that many Egyptians work in Saudi Arabia thus it is assumed that GT4 arrived in Saudi Arabia with employees from Africa and the Middle East [2,7,9]. This is further supported by the sequencing of the HCV core region [15].…”
Section: N Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…A recent Saudi survey conducted in Jeddah has reported that there is a lower prevalence of GT-2 (4.1%) and higher HCV genotype 4 (60.7%) [1]. Because GT4 is very common in Egypt (10%-15%) and that many Egyptians work in Saudi Arabia thus it is assumed that GT4 arrived in Saudi Arabia with employees from Africa and the Middle East [2,7,9]. This is further supported by the sequencing of the HCV core region [15].…”
Section: N Discussionmentioning
confidence: 99%
“…Chronic HCV infection accounts for 20% of hepatocellular carcinoma (HCC), and about 700,000 people die annually from complications related to HCV [6]. HCV is classified into seven genotypes (GT) and 67 subtypes such as 1a, 1b, 2a, 3a, 4a [3,7]. Globally, GT-1 is common in North America, South America, Western and Northern Europe, representing 46% of all HCV cases [7].…”
mentioning
confidence: 99%
See 3 more Smart Citations